Femininity and masculinity in Stephen Chifunyise’s written plays:the case of intimate affairs and muramu - Vhutuza, Ephraim (Journal of Performance and Creative Arts, 2016)
The article argues that masculinity and femininity should not be understood narrowly as mutually exclusive bipolar opposites. Every individual. female or male should he assessed on a continuum of femininity and masculinity qualities. Thus. it is the 'amount' or preponderance of either masculinity or femininity traits that vary from one individual to another in both males and females. We will also argue that not all females are necessarily feminine and that not all males are necessarily masculine. With close reference to the two written plays, we will further argue that femininity or masculinity should not he simplistically understood to be determined only by the process of socialisation. It will be argued that it is not only socialisation that determines one's masculinity or femininity as to suggest so is to not only be deterministic, but also essentialist. static and dichotomous. It will be concluded that masculinity or femininity in males and females is the outcome of one's willingness to conform or not conform to societal expectations and to some extent, the biology.